Effects of high-speed training on messenger RNA expression in two-year-old thoroughbred racehorses - Johnson, M. G.; Adam, E.; Watt, A.; Page, A. E. (Journal of Equine Veterinary Science, 2023)
Accumulating high-speed exercise has been identified as a significant risk factor for catastrophic injuries in racing Thoroughbreds. Injuries, regardless of severity, are a main cause of withdrawal from the racing industry, raising animal welfare concerns and resulting in significant economic losses. While most of the current literature focuses on injuries incurred during racing rather than training, the present study aims to help fill this gap. As such, peripheral blood was collected weekly, prior to exercise or administration of medication, from eighteen, two-year-old Thoroughbreds throughout their first season of race training. Messenger RNA (mRNA) was isolated and used to analyze the expression of 34 genes via RT-qPCR. Statistical analysis of the noninjured horses (n = 6) showed that 13 genes were significantly correlated with increasing average weekly high-speed furlong performance. Additionally, there was a negative correlation for CXCL1, IGFBP3, and MPO with both cumulative high-speed furlongs and week of training for all horses. Comparison of both groups showed opposing correlations between the anti-inflammatory index (IL1RN, IL-10, and PTGS1) and average weekly high-speed furlong performance. Furthermore, evaluation of training effects on mRNA expression during the weeks surrounding injury, showed differences between groups in IL-13 and MMP9 at -3 and -2 weeks prior to injury. While some previously reported relationships between exercise adaptation and mRNA expression were not noted in this study, this may have been due to the small sample size. Several novel correlations, however, were identified and warrant further investigation as markers of exercise adaptation or potential risk for injury.